Differential Response of Bovine Mature Nucleus Pulposus and Notochordal Cells to Hydrostatic Pressure and Glucose Restriction. (April 2020) - Saggese, Taryn; Thambyah, Ashvin; Wade, Kelly; McGlashan, Susan Read
Objective: The nucleus pulposus of the human intervertebral disc contains 2 cell types: notochordal (NC) and mature nucleus pulposus (MNP) cells. NC cell loss is associated with disc degeneration and this process may be initiated by mechanical stress and/or nutrient deprivation. This study aimed to investigate the functional responses of NC and MNP cells to hydrostatic pressures and glucose restriction. Design: Bovine MNP and NC cells were cultured in 3-dimensional alginate beads under low (0.4-0.8 MPa) and high (1.6-2.4 MPa) dynamic pressure for 24 hours. Cells were cultured in either physiological (5.5 mM) glucose media or glucose-restriction (0.55 mM) media. Finally, the combined effect of glucose restriction and high pressure was examined. Results: Cell viability and notochordal phenotypic markers were not significantly altered in response to pressure or glucose restriction. MNP cells responded to low pressure with an increase in glycosaminoglycan (GAG) production while high pressure significantly decreased ACAN gene expression compared with atmospheric controls. NC cells showed no response in matrix gene expression or GAG production with either loading regime. Glucose restriction decreased NC cell TIMP-1 expression but had no effect on MNP cells. The combination of glucose restriction and high pressure only affected MNP cell gene expression, with decreased ACAN, Col2α1, and ADAMTS-5 expression. Conclusion: This study shows that NC cells are more resistant to acute mechanical stresses than MNP cells and provides a strong rationale for future studies to further our understanding the role of NC cells within the disc, and the effects of long-term exposure to physical stresses.